1999
DOI: 10.1577/1548-8659(1999)128<0058:hghics>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

High Genetic Heterogeneity in Chum Salmon in Western Alaska, the Contact Zone between Northern and Southern Lineages

Abstract: Genetic relationships among 64 spawning populations of chum salmon Oncorhynchus keta in western Alaska were studied using allele frequency data from 40 protein-encoding loci.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
76
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(88 citation statements)
references
References 30 publications
12
76
0
Order By: Relevance
“…In fact, the SAMOVA results reveal a single collection group for each species that consisted of all or most of the Norton Sound and Kuskowkim River watersheds and the lower Yukon River. Other studies have described low heterogeneity among western Alaska salmon populations (e.g., Gharrett et al 1987;Wilmot et al 1994;Seeb and Crane 1999;Utter et al 2009). The locations of boundaries separating the coastal and inland collections are similar for each species and are identified as partial gene flow barriers.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In fact, the SAMOVA results reveal a single collection group for each species that consisted of all or most of the Norton Sound and Kuskowkim River watersheds and the lower Yukon River. Other studies have described low heterogeneity among western Alaska salmon populations (e.g., Gharrett et al 1987;Wilmot et al 1994;Seeb and Crane 1999;Utter et al 2009). The locations of boundaries separating the coastal and inland collections are similar for each species and are identified as partial gene flow barriers.…”
Section: Discussionmentioning
confidence: 92%
“…Glacial recession followed by isostatic rebound could have resulted in stream captures in both areas (e.g., a branch of the Chandalar River by the Koyukuk River and a branch of the Tanana River by the Kuskokwim River). Vicariance induced by glacial recession has been used to explain similar results for salmon elsewhere in Alaska (e.g., Gharrett et al 1987;Seeb and Crane 1999). Alternatively, the three barriers (and other barriers between the coastal and inland groups) may reflect post-glacial secondary contact.…”
Section: Discussionmentioning
confidence: 93%
“…For instance, Seeb and Crane (1999) studied allozyme variation in chum salmon (Oncorhynchus keta) and reported a contact zone between Beringian and Cascadian lineages across a 150 km wide stretch of the northwestern portion of the Alaska Peninsula. Chignik Lake falls within this zone on the southern portion of the Alaska Peninsula.…”
Section: Admixture Zone In the North Pacificmentioning
confidence: 99%
“…Chignik Lake falls within this zone on the southern portion of the Alaska Peninsula. Seeb and Crane (1999) also noted that this general area is thought to be a contact zone between two human aboriginal language groups: Aleut and Yu'pik (Muller-Beck 1967). O' Corry-Crowe et al (1997) and Westlake and O'Corry-Crowe (2002) used mtDNA to resolve major distinctions between populations within both beluga whales (Delphinapterus leucas) and harbor seals (Phoca vitulina) sampled north and south of the Alaska Peninsula and suggested that the peninsula may represent a major biogeographical boundary.…”
Section: Admixture Zone In the North Pacificmentioning
confidence: 99%
See 1 more Smart Citation